Macronutrient extraction curves of the onion crop - Gonçalves, Felipe Augusto Reis; Aquino, Priscila Maria de; Duarte, Luiz Otávio; Aquino, Rosiane Filomena Batista Almeida de; Reis, Marcelo Rodrigues dos; Aquino, Leonardo Angelo de (Semina: Ciências Agrárias, 2019)
This study aimed to determine the extraction curves and accumulation order of macronutrients of two onion cultivars. In commercial fields in the region of Alto Paranaíba, MG, Brazil, onion plants of the cultivars 'Optima' and 'Sirius' were collected during the cycle in 2014 and 2015 to determine dry matter and macronutrient accumulation. The yield was determined at harvest time. Three phases of dry matter and nutrient accumulations were observed. The first phase had a slow accumulation and was followed by a fast increment and subsequent stabilization in phases two and three, respectively, for most of the nutrients in both cultivars and years of cultivation. Duration and accumulated at each phase were different between cultivars and years of cultivation. The total and commercial bulb yield did not vary between cultivars but only between years of cultivation, with average values of 117 and 60 Mg ha?1 in 2014 and 2015, respectively. The partitioning of dry matter and macronutrients followed the same model for both cultivars and years of cultivation. Macronutrients with the largest partitioning for bulbs are P and S. The decreasing extraction order for both cultivars was K > Ca > N > P > Mg > S in 2014 and K > N > Ca > P > S > Mg in 2015.